Role of Lithium Carbonicum in Gout: A Case Report (Homoeopathy for All, 2025)
Gout is a metabolic disorder caused by serum uric acid crystal deposition on the joints. We present a case report of a patient age 38 years old male, who presented with pain in right big toe of lower limb with severe pain, redness, swelling, tender joint with anorexia, fever and skin eruptions. As gout typically affect the middle age male, but there are some lifestyle factors and dietary habits in its pathogenesis. There was no another history of any other disease. Patient came with raised ESR and Serum Uric Acid levels, so he was previously diagnosed with gout. We prescribed him Lithium Carbonicum 30/tds on the basis of presenting complaints and raised serum uric acid level. This case report highlights the homoeopathic management of gout with Lithium Carbonicum.
Keywords: Gout; SUA; MTP Joint; Lithium Carb; Case Report